New device production for preventive measures against the hallux-valgus deformity. Issue 4 (27th March 2011) - Urabe, Y; Kamiya, N; Yamanaka, Y; Shintaku, M
Abstract : Background: Many athletes have foot deformity of hallux-valgus. These deformities lead to decrease of foot function and sports performance. The authors were developed a new device for decrease the angle of hallux-valgus. This device was socks and in use underwear in sports activity and daily living. Objective: The purpose of this study was following four points. Does this device can change the hallux-valgus angle? Does this device can change the foot pain? Does this device influence centre of pressure (COP) of the foot? Does this device can decrease the deformity for long-term use? Design: Prospective and randomised controlled trial design. Setting: This study was clinical setting for athletes. Participants: The subjects were 34 female volunteer athletes. The hallux-valgus group was consisted 17 athletes, all who has hallux-valgus angle above 20° and complaint of foot pain. The control group was 17, all who has hallux-valgus angle below 19° and pain free of each foot. Intervention: The subjects were used this socks 3 months of their daily life and sports activities. Main outcome measurements: The hallux-valgus angle and COP of standing position were measured, and checked again after the 3 months. Results: The hallux-valgus angle was decreased 7.1° at instance of wearing the socks with hallux-valgus group and 5.5° with control group. The foot pain was decreased 50% at instance of wearing socks with hallux-valgus group and 70% decrease at 2.3 months uses the socks. The COP of the body was changed 3.7% forward on the foot of hallux-valgus group. The 2.3 months later, hallux-valgus angle was decreased 4.7° of average at the bare foot with hallux-valgus group. Conclusions: This study showed the hallux-valgus prevention socks were decreased not only deformity angle at instance but also use prolonged more angle decreased.